Chemicals industry’s initiatives for corporate social responsibility: some perspectives from academia - Lee, Khai Ern; Mazlin Mokhtar; Goh, Choo Ta; Lubna Alam; Mahathir Amir (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2018)
Chemicals industry is likely to become increasingly relevant in Malaysia. The government is playing its active role in regulating and enforcing legislation to monitor the activities throughout the chemical lifecycle. Chemicals industry itself is also ought to manage the risks associated with their activities through a holistic risk management framework. With the implementation of global regulations and policies, it is able to increase the competitiveness of chemicals industry in the global market and enhance protection of human health and the environment. Today’s chemicals industry should not merely focus on maximize their profit and meeting the needs of shareholders, focus should also be devoted to their social and environmental performances and meeting the needs of other key stakeholders including the community, customers, suppliers, and employees. Corporate social responsibility (CSR) thus has become a concern for chemicals industry. Various CSR emblematic initiatives, namely Responsible Care (RC), Product Stewardship (PS) and Extended Producer Responsibility (EPR) have been carrying out within chemicals industry. The implementation of such initiatives has become a way for chemical companies to advance social progress while also making a profit, and ultimately becomes a way for many businesses to sustain over the long-term.